Prevalence and factors associated with placental malaria in Lira District, Northern Uganda: a cross‑sectional study - Epuitai, Joshua; Ndeezi,Grace; Mukunya, David; Tumwine, James K. (Malaria Journal, 2024)
Malaria has a stable perennial transmission across Uganda. Placental malaria is associated with adverse maternal, fetal, and neonatal outcomes. The factors associated with placental malaria are poorly understood in the study setting. The aim of the study was to assess the prevalence of placental malaria and to determine its associated factors among parturient women in Lira District, Uganda. This was a cross-sectional study among 366 pregnant women who delivered at Lira Regional Referral Hospital. Data were collected from December 2018 to February 2019 using an interviewer-administered questionnaire. The variables were socio-demographic, obstetric characteristics, and malaria preventive practices. Standard Diagnostic Bioline Rapid Diagnostic Tests were used to detect placental malaria present in placental blood. Microscopy was used to quantify the grade of placental malaria parasitaemia. Logistic regression was used to assess factors associated with placental malaria. The mean age of the participants was 25.34 years (standard deviation [SD] 5.73). The prevalence of placental malaria was [4.4% (16/366) 95% CI (2.5 to 7.0)]. Of these, only 7/16 were positive on microscopy, with 2/7 having moderate parasitemia and 5/7 having mild parasitaemia. Women aged less than 20 years [AOR 3.48, 95% CI (1.13 to 10.72)], and those not taking iron supplements during pregnancy [AOR = 3.55, 95% CI (1.02 to 12.31)] were associated with an increased likelihood of having placental malaria.The prevalence of placental malaria was low in this setting. This may have reflected the low malaria transmission rates following intensive indoor residual spraying. Placental malaria infection was associated with younger age and not taking iron supplements during pregnancy. Public health measures need to scale up and emphasise adherence to malaria preventive measures during pregnancy especially among teenage mothers.